Levels in neurotransmitter precursor amino acids correlate with mental health in patients with breast cancer. (October 2015) - Hüfner, K.; Oberguggenberger, A.; Kohl, C.; Geisler, S.; Gamper, E.; Meraner, V.; Egeter, J.; Hubalek, M.; Beer, B.; Fuchs, D.; Sperner-Unterweger, B.
Highlights: Depression is a comorbidity in about 30% of patients with cancer. The study identifies a possible pathophysiological link between cancer and depression. Phenylalanine/tyrosine ratio was associated with "breast cancer" and "depression". Kynurenine/tryptophan ratio was associated with "breast cancer" and "state anxiety". The present results could be the basis for future treatment studies. Summary: Breast cancer is the most common cancer among females. Approximately 30% of cancer patients develop depression or depressive adaptation disorder within 5 years post diagnosis. Low grade inflammation and subsequent changes in neurotransmitter levels could be the pathophysiological link. In the current study we investigated the association of neurotransmitter precursor amino acids with a diagnosis of depression or state anxiety in 154 subjects suffering from breast cancer (BCA + ), depression (DPR + ), both or neither. Sociodemographic parameters, severity of depressive symptoms, and state anxiety (ANX) were recorded. Neopterin, kynurenine/tryptophan and phenylalanine/tyrosine were analysed by HPLC or ELISA. Significantly higher serum neopterin values were found in DPR + patients ( p  = 0.034) and in ANX + subjects ( p  = 0.008), as a marker of Th1-related inflammation. The phenylalanine/tyrosine ratio (index of the catecholamine pathway) was associated with the factors "breast cancer" and "depression" and their interaction (all p  < 0.001); it was highest in the DPR + BCA + group. The kynurenine/tryptophan ratio (index of the serotonin pathway) was significantly associated with the factors "breast cancer" and "state anxiety" and their interaction ( p  < 0.001, p  = 0.026, p  = 0.02, respectively); it was highest in the ANX + BCA + group. In BCA + patients kynurenine/tryptophan ratios correlated with severity of state anxiety ( r  = 0.226, p  = 0.048, uncorrected) and phenylalanine/tyrosine ratios with severity of depressive symptoms ( r  = 0.376, p  < 0.05, corrected). In conclusion, levels of neurotransmitter precursor amino acids correlate with mental health, an effect which was much more pronounced in BCA + patients than in BCA − subjects. Aside from identifying underlying pathophysiological mechanisms, these results could be the basis for future treatment studies: in BCA + patients with depression the use of serotonin-noradrenaline reuptake inhibitors might be recommended while in those with predominant anxiety selective serotonin reuptake inhibitors might be the treatment of choice.